2021
DOI: 10.1103/physreva.104.033308
|View full text |Cite
|
Sign up to set email alerts
|

Emission of particles from a parametrically driven condensate in a one-dimensional lattice

Abstract: We investigate particle emission, driven by periodically modulating the interaction strength, from three coupled Bose-Einstein condensates in a one-dimensional lattice. Within perturbative analyses, which lead to the regimes of instabilities for different modes, we not only obtain two main frequencies, under which the system can emit a large particle jet, but also find that the emission is distinctly intermittent rather than continuous. The time evolution of the trapped particles exhibits a stairlike decay, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…[27,28] We introduce, in the context of mean-field approach, the expectation values of a j≥0 = â j≥0 and b j≥0 = b j≥0 , where their squares represent the number of particles on site j. In the fireworks experiments, [17,[19][20][21][22] the average dc scattering lengths were generally kept small, and in a previous work we have demonstrated that a finite U did not qualitatively change the results, [27] thus we take the limit of U = 0 for simplicity. We begin from the equilibrium at g = 0, which leads to the Heisenberg equations of motion for a j≥0 (taking units where h = 1)…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[27,28] We introduce, in the context of mean-field approach, the expectation values of a j≥0 = â j≥0 and b j≥0 = b j≥0 , where their squares represent the number of particles on site j. In the fireworks experiments, [17,[19][20][21][22] the average dc scattering lengths were generally kept small, and in a previous work we have demonstrated that a finite U did not qualitatively change the results, [27] thus we take the limit of U = 0 for simplicity. We begin from the equilibrium at g = 0, which leads to the Heisenberg equations of motion for a j≥0 (taking units where h = 1)…”
Section: Theoretical Modelmentioning
confidence: 99%
“…where G j1 (t) = i j−2 jJ j (2J l t)θ (t)/J l t is the time-domain Green's function with J n (z) being the Bessel function of the first kind. [27] To describe the nonlinear dynamics of the system, one can directly solve Eq. (2) through Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We can numerically solve these equations, using the techniques discussed in Ref. [18]. Equivalently, we can truncate the leads and directly solve Eqs.…”
Section: Fig 1 (Color Online) Schematic Of the 1d Infinite Latticementioning
confidence: 99%
“…In a previous work we analyzed a minimal model of these experiments, which demonstrated how the modulated interactions lead to particle emission [18]. The model consists of a semi-infinite 1D lattice where a deep local potential confines a condensate to the boundary site.…”
Section: Introductionmentioning
confidence: 99%